A comparative study between sacral neuromodulation and intravesical botulinum toxin injection for patients with refractory overactive bladder. Issue 2 (2nd April 2020) - Al-Azzawi, Issam S.; Al-Hindawi, Haider T.
ABSTRACT: Objective: To compare the efficacy, safety, patient compliance and quality of life (QoL) (early and at 6 months after treatment), in a group of Iraqi female patients with refractory overactive bladder (OAB), treated with intradetrusor botulinum toxin A (BTX) injections vs sacral neuromodulation (SNM). Patients and methods: A prospective, clinical interventional study of 37 female patients assessed by history, physical examination, voiding diary, ultrasonography (US), and urodynamics. The patients were assigned to one of two groups: Group 1, treated with cystoscopic BTX injections; and Group 2, treated with SNM. Response to treatment was assessed by voiding diary, the Treatment Benefit Scale, a modified Quality of Life scale, urine culture, and abdominal US. Results: The mean age of the patients in Group 1 (BTX) was 43.8 years and in Group 2 (SNM) was 37.2 years. OAB-wet was diagnosed in 11 patients in Group 1 and 10 in Group 2. At the 6-month follow-up there were 14/16 and 12/15 positive responders, in groups 1 and 2, respectively; with no major complications. All the responders had a significant improvement in their overall QoL after both types of treatment. Conclusions: Both BTX and SNM, in our experience, were safe and effective in managing our patients with refractory OAB after 6 months of follow-up, which was also reflected by an improvement in their QoL. Abbreviations: BTX: botulinum toxin A; IPG: implantable pulse generator; OAB: overactive bladder; PVR: post-void residual urine; QoL: quality of life; SNM: sacral neuromodulation; UDS, urodynamics; UI, urinary incontinence